Effectiveness of Shaping Techniques in Promoting Independence in Children with Intellectual Disabilities - Kusumaningrum, Yesita Ragil; Fitriani, Fitriani (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
According to the World Health Organization (WHO), 12% of children worldwide, or over 450 million, had mental retardation in 2019, and that number is expected to rise to 15% by 2020 (Schalock & Luckasson, 2021), As per the Special Education Statistics of Indonesia for the year 2019–2020, 144,102 individuals, or 56% of the population, were enrolled in both public and private special schools. With 12,007 children, Central Java Province comes in second (Pusdatin Kemendikbud Indonesia, 2020). In 2020, the Grobogan Regency had a population density of 736 persons per km³, and 1,596 of those children had intellectual disabilities (Central Java Village Information System, 2022). Objective: to use shaping techniques to assess how much mentally retarded children's self-development education has become more independent. Research methods: This study employed a quasi-experimental pretest-posttest design involving 45 children with intellectual disabilities. Results show a significant improvement in independence after intervention, with independence scores increasing from 55.6% to 75.6% (p < 0.05).” Conclusion: The effectiveness of modeling methods and engineering in guiding the self-development of mentally retarded children toward independence